2015
DOI: 10.1016/j.cct.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Using e-technologies in clinical trials

Abstract: Clinical trials have been slow to incorporate e-technology (digital and electronic technology that utilizes mobile devices or the Internet) into the design and execution of studies. In the meantime, individuals and corporations are relying more on electronic platforms and most have incorporated such technology into their daily lives. This paper provides a general overview of the use of e-technologies in clinical trials research, specifically within the last decade, marked by rapid growth of mobile and Internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
111
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 130 publications
0
111
1
3
Order By: Relevance
“…Furthermore, we know little about the people who download depression treatment apps in terms of symptom severity, disability, and use of more traditional mental health services. Although a few proof-of-concept studies have found that adherence to depression app guidelines tends to be poor over time [17-21], there is little information about the relative use patterns between different types of apps. We conducted a large-scale RCT (NCT00540865) of 3 different depression apps to answer the following questions: (1) Who downloads mobile apps for depression?…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we know little about the people who download depression treatment apps in terms of symptom severity, disability, and use of more traditional mental health services. Although a few proof-of-concept studies have found that adherence to depression app guidelines tends to be poor over time [17-21], there is little information about the relative use patterns between different types of apps. We conducted a large-scale RCT (NCT00540865) of 3 different depression apps to answer the following questions: (1) Who downloads mobile apps for depression?…”
Section: Introductionmentioning
confidence: 99%
“…The VACC-Tool facilitates the consistent documentation of adverse events over time. Dynamic data entry systems using mobile devices are likely to become the cornerstone of clinical research in the near future [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…It based on technology as an add-on, substitute, and replacement for standard care. Technology-enhanced treatment interventions are mainly Webbased versions of evidence-based, in-person treatment components such as CBT and MET [63].…”
Section: E-treatmentsmentioning
confidence: 99%